Inotodiol induces hepatocellular carcinoma apoptosis by activation of MAPK/ERK pathway - Yushuang Xing; Di Jia; Xinping Zhu; Jialu Yang; Zhipeng Gao; Nana Meng; Haohao Xu; Mengxiao Wang; Shijun Chang; Mingqian Zhao; Shanbo Zhang; Zichen Mu; et al. (PLoS ONE, 2025)
Hepatocellular carcinoma(HCC) has a high mortality and morbidity rate and seriously jeopardizes human life. Chemicals and chemotherapeutic agents have been experiencing problems such as side effects and drug resistance in the treatment of HCC, which cannot meet the needs of clinical treatment. Therefore, finding novel low-toxicity and high-efficiency anti-hepatocellular carcinoma drugs and exploring their mechanisms of action have become the current problems to be solved in the treatment of HCC. Several studies have reported anticancer effects of inotodiol. This study focuses on the anticancer effect of inotodiol in HCC cells and its molecular mechanism, aiming to explore its anticancer effect in depth. The CCK8 assay was utilized to assess cell viability, the scratch assay was utilized to detect migration ability, the clone formation assay was utilized to detect clonogenic ability, and flow cytometry was utilized to analyze apoptosis and cell cycle. Animal experiments was utilized to verify the inhibitory effect of inotodiol on HCC. Meanwhile, western blotting was utilized to detect proteins associated with apoptosis, cell cycle and MAPK/ERK pathway. These results showed that inotodiol has the ability to promote apoptosis, as well as inhibit the ability of cell proliferation, migration, and clonogenic ability. The cell cycle was arrested in G1 phase, when the expression of CDK2, CDK4, CDK6 and Cyclin D were inhibited. In addition, inotodiol showed to induce apoptosis, characterized by an increase in Bax expression, a decrease in Bcl-2, Bcl-XL and MCL1 expression, the initiation of cleaved PARP1 and cleaved caspase 3, and inhibition of the MAPK/ERK pathway. Animal studies demonstrated that inotodiol possessed the ability to suppress tumor growth in nude mice models, at the same time, there was no significant impact on the body weight and organs of the mice. In conclusion, the findings presented herein compellingly suggest that inotodiol may serve as a promising candidate for the treatment of hepatocellular carcinoma (HCC).